Screening 35 million for hypertension and diabetes mellitus through public system: experiences of Tamil Nadu, India - Selvavinayagam, T. S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Non communicable diseases (NCDs) is one of major public health challenge to be handled across the world particularly in low and middle-income countries. Government of Tamil Nadu in partnership with World Bank attempted to tackle this issue. Our State’s experience in implementing NCD control program from piloting and then expanding it to entire state with learning’s are described in this article. Methods: A comprehensive NCD control program with four major interventions namely clinic, school, community and workplace based interventions covering hypertension and diabetes that was implemented successfully through public health system in Tamil Nadu is elaborated. Results: The program yielded a magnificent performance in screening around 4 crore persons and the challenges in implementing the program covering human resources, drugs and reagents logistics, protocols, awareness creation, data capturing and effective monitoring etc. are highlighted. Conclusions: This knowledge in implementing NCD control program in Tamil Nadu will be useful to other states in India as well as in other low and middle-income countries in planning their NCD programs.